PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN PT ELECTRONIC CITY INDONESIA TBK PERIODE 2015-2024 - Sindi Septira; Taufik Awaludin (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the effect of cash turnover and accounts receivable turnover on profitability at PT Electronic City Indonesia Tbk during the period 2015–2024. Profitability in this study is measured using Return on Assets (ROA). The research method employed is a quantitative approach using secondary data obtained from the published financial statements of PT Electronic City Indonesia Tbk for the period 2015–2024.The data analysis techniques used include classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), t-test (partial), and F-test (simultaneous). The results of the classical assumption tests indicate that the data meet the requirements of normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results of multiple linear regression analysis produced the equation: Y = -0.021 + 0.022X₁ + 0.473X₂. The t-test results show that cash turnover has no significant effect on profitability, with a t-value of 0.478 and a significance value of 0.647 > 0.05. Accounts receivable turnover also has no significant effect on profitability, with a t-value of 0.430 and a significance value of 0.680 > 0.05. Furthermore, the F-test results indicate that cash turnover and accounts receivable turnover simultaneously have no significant effect on profitability, with an F-value of 0.145 and a significance value of 0.867 > 0.05.Based on the findings, it can be concluded that cash turnover and accounts receivable turnover, both partially and simultaneously, do not have a significant effect on profitability at PT Electronic City Indonesia Tbk during the period 2015–2024. Keywords: Cash Turnover, Receivables Turnover, Profitability, Return On Assets (ROA).